PEMBAKARAN FERRALSOL DAN APLIKASINYA UNTUK PENJERNIHAN MINYAK GORENG SISA PAKAI - Suhartana, Suhartana (BERKALA FISIKA, 2007)
Ferralsol is tropical type land, which exploited as rice field farm and plantation. Other benefit which can be taken away from  this ferrasol  if burned hence will be able to make liquid cleaner material. Composition of ferralsol is ferralsol orthic and ferralsol plinthic. If burned is good for purification liquid material, inorganic and also organic material. In this research result of combustion from ferralsol, used to make clear ex- cooking oil. Result of which scored a number of peroxide go down 12,75 %, number of acid also go down 8,33 %,   by ferralsol, and a number of peroxide go down 19,45 %, number of acid also go down 10,42 % by burning ferralsol   but with both ex- cooking  oil color become clear progressively.   Keyword: ferralsol, liquid cleaner material